Radiation-induced and neurofibromatosis-associated malignant peripheral nerve sheath tumors (MPNST) have worse outcomes than sporadic MPNST. (August 2019) - Miao, Ruoyu; Wang, Haotong; Jacobson, Alex; Lietz, Anna P.; Choy, Edwin; Raskin, Kevin A.; Schwab, Joseph H.; Deshpande, Vikram; Nielsen, G. Petur; DeLaney, Thomas F.; Cote, Gregory M.; Hornicek, Francis J.; et al.
Highlights: Both radiation-induced and neurofibromatosis-associated MPNSTs have poorer prognosis than sporadic MPNSTs. Complete resection of the tumor is a significant prognostic factor for MPNST. Surgery with adjuvant radiotherapy is related to improved local control in patients with positive surgical margins. Abstract: Background: Malignant peripheral nerve sheath tumors (MPNST) may be sporadic or associated with neurofibromatosis or prior radiation. MPNST may behave aggressively with a high rate of local recurrence and distant metastasis. Methods: In an IRB approved protocol, we reviewed the clinical characteristics, treatment, and outcomes of 280 patients treated for MPNST at Massachusetts General Hospital (MGH) between 1960 and 2016. Results: There were 138 men and 142 women with a median age of 41 (range: 3–95) years. Tumors were classified as neurofibromatosis-associated (nfMPNST, n  = 77), radiation-induced (rMPNST, n  = 21), or sporadic (sMPNST, n  = 182) MPNST. The median time to development of rMPNST from prior radiation was 15 years. With a median follow-up of 43.1 months, the median overall survival (OS) was 65.3 months. Older age, nfMPNST, rMPNST, increased tumor size, lymph node involvement, metastatic disease, intermediate to high grade, radiotherapy alone, and R2 resection were related to worse OS, whereas surgery with radiotherapy was associated with improved OS. Among the 251 patients without metastasis, nfMPNST, rMPNST, and increased tumor size were correlated with worse metastasis-free survival; nfMPNST, radiotherapy alone, and R1/R2 resection were associated with local recurrence, whereas surgery with adjuvant radiotherapy was related to improved local control in patients with R1/R2 resection. Conclusions: Both radiation-induced and neurofibromatosis-associated MPNSTs have poorer prognosis than sporadic MPNSTs. Complete resection of the tumor is a significant prognostic factor for MPNST. The addition of radiotherapy after surgery should be considered especially when the surgical margins are positive.